2011
DOI: 10.1007/s10535-011-0030-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of abiotic stresses on the NADP-dependent malic enzyme in the leaves of the hexaploid wheat

Abstract: The objective of this study was to examine the effects of different abiotic stresses on the activity of an NADPdependent malic enzyme (NADP-ME) and the corresponding gene transcription in the leaves of the hexaploid wheat (Triticum aestivum L.) The activity of the NADP-ME enzyme was increased by water stress (20 % polyethylene glycol 6000), low temperature (4 °C), darkness, salinity (200 mM NaCl), abscisic acid and salicylic acid. The transcription of the TaNADP-ME1 gene decreased in response to all of the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Previous studies reported that the accumulation of enolase was upregulated in different varieties under drought stress and other abiotic stresses [ 53 , 55 57 ]. The activity of the NADP-dependent malic enzyme (NADP-ME) was typically enhanced under various stresses, including those caused by PEG, SA, cold, darkness and NaCl, and RT-PCR showed that the transcript accumulation of NADP-ME in the leaves was distinctly affected by various stresses [ 58 ]. The upregulated accumulation of cytosolic aconitase plays a role in mediating oxidative stress and regulating cell death, which might enhance the tolerance of wheat to drought stress [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the accumulation of enolase was upregulated in different varieties under drought stress and other abiotic stresses [ 53 , 55 57 ]. The activity of the NADP-dependent malic enzyme (NADP-ME) was typically enhanced under various stresses, including those caused by PEG, SA, cold, darkness and NaCl, and RT-PCR showed that the transcript accumulation of NADP-ME in the leaves was distinctly affected by various stresses [ 58 ]. The upregulated accumulation of cytosolic aconitase plays a role in mediating oxidative stress and regulating cell death, which might enhance the tolerance of wheat to drought stress [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…UV-B radiation [40] . Increased NADP-ME activity in transgenic Arabidopsis by osmotic stress induced a greater salt tolerance [41] , wheat NADP-ME also responded to various abiotic stresses [42] . Heat shock proteins are well known to be induced by all kinds of stress conditions and are efficient to protect cells against these stresses.…”
Section: Discussionmentioning
confidence: 98%
“…Salicylic acid plays an important role in modulating plant responses to abiotic and biotic stresses (Senaratna et al 2000, Ding et al 2002, Tasgin et al 2006, Wen et al 2008, Fu et al 2011, Saruhan et al 2012, Mutlu et al 2013b.…”
Section: Discussionmentioning
confidence: 99%